THE EFFECTIVENESS OF TASK-BASED TEACHING AND LEARNING (TBTL) IN MODERN EDUCATION - Xalilova Mohichehra,; Abdullayeva Ruxsora, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Task-Based Teaching and Learning (TBTL) has emerged as a cornerstone of modern  pedagogical  methodology,  shifting  the  educational  focus  from  traditional, teacher-centered rote learning to a more dynamic, student-centric approach. This article explores the theoretical foundations and practical applications of TBTL, emphasizing its  role  in  developing  communicative  competence  and  real-world  problem-solving skills. The core objective of TBTL is to engage learners in meaningful tasks where language or knowledge is used as a tool to achieve a specific outcome rather than as an isolated subject of study. By analyzing the structural framework of TBTL—comprising pre-task,  task  cycle,  and  post-task  phases—this  study  highlights  how  the  method fosters learner autonomy and motivation. Furthermore, the article discusses the benefits of TBTL in enhancing social interaction and critical thinking, while also addressing common  challenges  such  as  time  constraints  and  assessment  complexities  in  large classrooms.  Through  practical  examples  in  English  language  teaching  and  other disciplines like history and mathematics, the research demonstrates that TBTL prepares students  for  real-life  challenges  by  bridging the  gap between  theoretical  classroom knowledge  and  practical  application.  Unlike  traditional  methods  that  prioritize grammatical accuracy through rote memorization, TBTL focuses on the completion of meaningful tasks as the primary unit of instruction. The study examines the impact on student  motivation,  autonomy,  and  the  development  of  practical  communicative competence.  Ultimately,  the study  concludes  that  the  integration  of  TBTL  into  the curriculum is essential for developing active, independent, and creative individuals capable  of  thriving  in  a  globalized  society.  The  findings  suggest  that  a  holistic approach, integrating  cognitive development  with social  awareness, is essential  for fostering genuine communicative autonomy in diverse linguistic contexts.